Small area parallel Chien search architectures for long BCH codes. - Yanni Chen (IEEE Transactions on VLSI systems)
To implement parallel BCH (Bose-Chaudhuri-Hochquenghem) decoders in an area-efficient manner, this paper presents a novel group matching scheme to reduce the Chien search hardware complexity by 60% for BCH(2047, 1926, 23) code as opposed to only 26% if directly applying the iterative matching algorithm. The proposed scheme exploits the substructure sharing within a finite field multiplier (FFM) and among groups of FFMs.